What is the Long Run Growth Rate of the East Asian Tigers? - B. Bhaskara Rao; Artur Tamazian; Rup Singh (Economics and Econometrics Research Institute (EERI), 2010)
New panel data estimates for the four East Asian Tigers show that the contribution of total factor productivity (TFP) to growth is much higher than past estimates. An extended production function with learning by doing implies that TFP is about 3.5% and these countries will grow at this rate in the long run.
Keywords: O1; N1; 330; Asian Tigers; Systems Dynamic GMM; Growth Accounting; Factor Accumulation as Residual